Полковник против полковника: [роман] / Максим Шахов - Шахов Максим Анатольевич (Спецназ, 2009)
Экземпляры: ЦБ (20110512) / Инвентарный номер: 43350 / Цена: 101.00 / Авт.знак: Ш 32 / ББК: 84(2Рос=Рус)6